2023
DOI: 10.3390/v16010049
|View full text |Cite
|
Sign up to set email alerts
|

Subconfluent ARPE-19 Cells Display Mesenchymal Cell-State Characteristics and Behave like Fibroblasts, Rather Than Epithelial Cells, in Experimental HCMV Infection Studies

Preethi Golconda,
Mariana Andrade-Medina,
Adam Oberstein

Abstract: Human cytomegalovirus (HCMV) has a broad cellular tropism and epithelial cells are important physiological targets during infection. The retinal pigment epithelial cell line ARPE-19 has been used to model HCMV infection in epithelial cells for decades and remains a commonly used cell type for studying viral entry, replication, and the cellular response to infection. We previously found that ARPE-19 cells, despite being derived from an epithelial cell explant, express extremely low levels of canonical epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…The ARPE-19 cell line is a commonly used retinal epithelial cell line for biochemical and virological studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Despite being derived from a retinal epithelium explant 20 , ARPE-19 cells exhibit cell culture characteristics that diverge significantly from primary retinal epithelial cells [21][22][23][24][25] . Most importantly, ARPE-19 cells exhibit strong density-dependent changes in their epithelial phenotype 20,21,26,27 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ARPE-19 cell line is a commonly used retinal epithelial cell line for biochemical and virological studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Despite being derived from a retinal epithelium explant 20 , ARPE-19 cells exhibit cell culture characteristics that diverge significantly from primary retinal epithelial cells [21][22][23][24][25] . Most importantly, ARPE-19 cells exhibit strong density-dependent changes in their epithelial phenotype 20,21,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that long periods of high confluency culture are required for ARPE-19 cells to establish a functional epithelial phenotype 20,21,23,[27][28][29] . After two to four months of high density culture, ARPE-19 cells turn on expression of epithelial (e.g., CDH1 and EPCAM) and visual cycle (e.g., RPE1, LRAT, RDH5, and RDH10) genes 21,23,27 ; assume a cobblestone epithelial morphology 20,23,27 ; establish apico-basal polarization 20,28,29 ; and display high trans-epithelial resistance (a measure of barrier function) 20,[27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations